Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
- 3 (2x + 1) - 4x + 45
= - 6x - 3 - 4x + 45
= - 6x - 4x - 3 + 45
= - 10x + 42
Hope it helps ⚜
- 3 (2x + 1) - 4x + 45
= - 6x - 3 - 4x + 45
= - 6x - 4x - 3 + 45
= - 10x + 42
Hope it helps ⚜
Answer:
[tex]\large\boxed{\boxed{\underline{\underline{\maltese{\pink{\pmb{\sf{\: Solution : \:-10x + 42}}}}}}}}[/tex]
Step-by-step explanation:
[tex]\sf{-3(2x + 1) - 4x + 45}\\\\\sf{Multiply \: the \: numbers : -3(2x + 1)}\\\\\sf{=( -3 * 2x) +( -3*1 )- 4x + 45}\\\sf{= -6x - 3 - 4x + 45}\\\\\sf{Rearrange \: the \: terms \: and \: do \: the \: operations} \\\\\sf{= -6x - 4x - 3 + 45}\\=\large{\boxed{\tt{ -10x + 42}}}\\[/tex]
_______
Hope it helps!
[tex]\mathfrak{Lucazz}[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.